Transcend socioeconomic status constraints to mathematics and science achievement by collaborative problem-solving: The female people-smartness hypothesis - Chiu, Mei-Shiu (Frontiers in Psychology, 2022)
The relationship between socioeconomic status (SES) and (mathematics and science) achievements is a robust phenomenon and is stronger for females. This study examines the female people-smartness (FPS) hypothesis, which addresses the reasons why females are more responsive to SES and posits that using females’ strengths of people-smartness can assist females to overcome SES constraints. This study used data from the student surveys of the Program for International Student Assessment in 2015. The results of the general linear model analysis revealed that females are better at collaborative problem-solving (CPS) and reading, while males are better at mathematics and science. Structural equation modelling revealed that the effect of SES on (mathematics and science) achievement is higher for females than for males. CPS can reduce the effect of SES on achievement. The findings generally support the FPS hypothesis and suggest that CPS-related competences should be emphasized and exercised to transcend SES constraints, especially for females in STEM curricula, studies and careers.